1991
DOI: 10.1159/000284698
|View full text |Cite
|
Sign up to set email alerts
|

A Functional-Dimensional Approach to Depression: Serotonin Deficiency as a Target Syndrome in a Comparison of 5-Hydroxytryptophan and Fluvoxamine

Abstract: H.M. van Praag has been suggesting a reappraisal of syndromes in psychiatry for over 20 years. He has tried to define syndromes originating from the same biochemical disorder. He has denoted this concept as ‘functional psychopathology’. As an example of such a functional syndrome, he has cited the serotonin-shortage syndrome which unifies various psychiatric symptoms under a new point of view. The treatment of the serotonin-shortage syndrome is best served by psychopharmaca which raise the metabolism of seroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 59 publications
0
9
0
2
Order By: Relevance
“…Investigators have also done at least 5 active comparator studies (Table 3). Two of these studies failed to show any difference between 5-HTP and the comparator, imipramine (Angst et al, 1977), or fluvoxamine (Poldinger et al, 1991), while 2 determined that 5-HTP was less effective than tranylcypromine for treatmentresistant depression (Nolen et al, 1985(Nolen et al, , 1988. One compared 5-HTP alone versus 5-HTP and a peripheral decarboxylase inhibitor (PDI), with neither group showing much improvement (Brodie et al, 1973).…”
Section: Clinical Evidence For Antidepressant Efficacy Of 5-hydroxytrmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigators have also done at least 5 active comparator studies (Table 3). Two of these studies failed to show any difference between 5-HTP and the comparator, imipramine (Angst et al, 1977), or fluvoxamine (Poldinger et al, 1991), while 2 determined that 5-HTP was less effective than tranylcypromine for treatmentresistant depression (Nolen et al, 1985(Nolen et al, , 1988. One compared 5-HTP alone versus 5-HTP and a peripheral decarboxylase inhibitor (PDI), with neither group showing much improvement (Brodie et al, 1973).…”
Section: Clinical Evidence For Antidepressant Efficacy Of 5-hydroxytrmentioning
confidence: 99%
“…Antidepressant drug trials are said to suffer from a lack of assay sensitivity (Temple & Ellenberg, 2000). Among the active-controlled studies shown in Table 3, there are 2 studies (Angst et al, 1977;Poldinger et al, 1991) in which 5-HTP appeared to perform equally to the active comparator. However, because these studies lacked placebo arms, their interpretation is problematic.…”
Section: Strength Of Efficacy Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 5-HTP was administered to hundreds of patients at doses ranging from 50 to 600 mg per day (in some cases up to 3250 mg per day) for the treatment of various types of depression, fibomyalgia, obesity, chronic headaches (migraines) and insomnia (Sano, 1971a(Sano, ,b, 1972Wyatt et al, 1971;Fujiwara and Otsuki, 1973;Matussek et al, 1974;Takahashi et al, 1975;Angst et al, 1977;Nakajima et al, 1978;van Hiele, 1980;Kaneko et al, 1979;van Praag et al, 1972van Praag et al, , 1974Brodie et al, 1973;Barlet and Pailard, 1973;Guilleminault et al, 1973;Lopez-Ibor Alino et al, 1976;Soulairac and Lambinet, 1977;Mendlewicz and Youdim, 1980;Boiardi et al,1981;Bono et al, 1984;Longo et al, 1984;De Benedittis and Massei, 1985;Kahn and Westenberg, 1985;Titus et al, 1986;Byerley et al, 1987;De Giorgis et al, 1987;Conte, 1988;Zmilacher et al, 1988;Westenberg and den Boer, 1989;Caruso et al, 1990;Den Boer and Westenberg, 1990;Agren et al, 1991;Maissen and Ludin, 1991;Poldinger et al, 1991;Cangiano et al, 1992;Puttini and Caruso, 1992;Nicolodi and Sicuteri, 1996). In all these studies, no adverse reactions related to EMS were noted, nor there were any other significant ...…”
Section: Clinical Studies With 5-hydroxy-l-tryptophanmentioning
confidence: 99%
“…In suicidal tendencies, the role of serotonin system is of the greatest importance and numerous post-mortem investigations had revealed lower concentrations of serotonin and its main metabolite 5-hydroxyindolacetate acid (5-HIAA) in brainstem, nuclei raphe, putamen and hypothalamus [7]. Some research show that lower levels of thrombocyte serotonin are connected with suicidal behaviour of depressive patients [8]. Numerous investigations have shown that, among the patients who had suffered a myocardial infarction or other diseases of cardiovascular system we can find depressive symptoms in the frame of depressive reaction, but also a real depression in its fully-blown clinical form.…”
Section: Introductionmentioning
confidence: 99%